2021
DOI: 10.3390/nu14010050
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health-Related Physical Fitness and Risk of Dyslipidemia in University Staff: A Cross-Sectional Study and a ROC Curve Analysis

Abstract: Background: This study aimed to assess the relationship between dyslipidemia (DL) risk and health-related physical fitness (HPF) and evaluated the prognostic value of HPF for risk of DL. Methods: A total of 776 university staff members were recruited, of which 407 were females, and 369 males. Blood samples and HPF tests were collected from all participants after 12 h fasting. Results: The prevalence of DL was 41.77% and 51.49% in female and male university staff members, respectively, and there was no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
2
10
0
Order By: Relevance
“…In the present study, overweight, general and central obesity were the significant risk factors for dyslipidemia. Similar findings were reported in previous studies [47][48][49][50]. Furthermore, low or inadequate physical activities were associated with the risk of dyslipidemia in our study.…”
Section: Plos Onesupporting
confidence: 93%
“…In the present study, overweight, general and central obesity were the significant risk factors for dyslipidemia. Similar findings were reported in previous studies [47][48][49][50]. Furthermore, low or inadequate physical activities were associated with the risk of dyslipidemia in our study.…”
Section: Plos Onesupporting
confidence: 93%
“…Also, we found that LAP was a bene cial factor in predicting the incidence of dyslipidemia. Recently, Zhou, Y et al, showed that LAP was more associated with dyslipidemia than BMI among university staff in a cross-sectional study (34). It has been stated that the BRI's potential role to predict dyslipidemia is comparable with BMI but not stronger (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that exercise has beneficial effects on serum lipid metabolism in healthy individuals and also in those with chronic illnesses [ 11 ]. No matter which form of activity is chosen, i.e., aerobic exercises, strength training, or high-intensity interval training, and whether long-term or short-term, PA promotes lipid metabolism by increasing HDL-C, and decreasing LDL-C, TC, and TG [ 12 ].…”
Section: Introductionmentioning
confidence: 99%